LEARNING CENTER UNIVERSITAS LAMBUNG MANGKURAT DI BANJARBARU - Mailindasari, Rizki; wastuty, Prima widia (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
The rapid development of technology and information lately affects the way we do things. Along with the existence of remote communication technology makes the work can be done remotely (teleworking). This is the reason for the changing way students learn lately. Students can study anywhere As a result is the decline of academic culture in the campus area because students choose to do learning activities off campus. However, Lambung Mangkurat University as a college has not been able to accommodate the maximum student learning activities outside of college time. Therefore, the Learning Center is needed as a support for learning and academic culture in the campus area. The architecture programming method was chosen as the design method. Programming architecture method is divided into five processes namely goals, facts, concept, needs, and problems. Architectural programming methods pay close attention to the problems in design. Generation Z is the dominant generation in universities today so the trend of learning Generation Z becomes a reference in design. Flexible Learning concept is a Learning Center concept that accommodates students' flexible learning. Flexible Learning is in accordance with generation Z learning trends that have flexibility in learning space, learning media, learning time, and learning style.